Teodosio Fernández. El teatro chileno contemporáneo (1941-1973) . Madrid, Ed. Playor, 1982 - González Boixo, José C. (Estudios Humanísticos. Filología, 1984)
Teodosio Fernández. El teatro chileno contemporáneo (1941-1973)